Histological investigation for the effect of botulinum toxin B inoculation in the gluteal group muscles of the thigh on the femoral bone of albino rabbits - S. M. Abdulateef; R. H. Thamer; A. K. Obayes (Regulatory Mechanisms in Biosystems, 2025)
Botulinum toxin B is an attenuated toxin produced by the bacterium Clostridium botulinum used in non-surgical cosmetic operation s and for correcting skin wrinkles. This article was designed to describe t he effect of denervated hind limb skeletal mu s cle impact on the femur bone of albino rabbits . Twenty-five male animals were enrolled in the five study groups . Five rabbits served as the control group, were given only distilled water and sacrificed at the end of the study for histological study. The re maining 20 rabbits were inoculat ed with a single dosage of b otulinum toxin B (8 IU) between the gluteal muscle group and the b iceps femoris muscle of the thigh, and each group of five w as sacrificed sequentially on day 10, day 15, day 30, and day 45 after the i noculation. Samples of femur bone were removed from the dissected animals. The microscopic examination of femur bone sections of the experimental 1st group showed an irregular endosteum border and narrowed bone collar. Animals from the experimental 2nd group showed remnant lacunae of hyaline cartilage and atrophied osteocytes. In the experimental 3rd group, results showed increased cavities within the bone matrix. In the experimental 4th group, the microscopic examination revealed the diminish ed periosteal membrane to the endosteum, atrophied lacunae, surrounded with irregular periosteum. The femoral bone displayed numerous histological changes due to the flaccid paralysis of the gluteal group muscles (disused muscles of the hi n d l imb) of the thigh caused by a single botulinum toxin B dose.